MINIMNYA ETIKA GENERASI MUDA INDONESIA DI ERA MILENIAL - Jamaludin Rumi; Cantika Putri Pores S; Tio Aquandri Siringo Ringo; Oktarini Fajriah; Elsa Pretty Simanjuntak; Elsa Meriska; Priska Melisa (CV. ADIBA AISHA AMIRA, 2023)
The modern era is an era where there is a lot of development, be it cultural development, educational development or technology. But of course, the modern era does not always have a good impact on life. In today's global era, there are many moral problems in the younger generation that are not in accordance with the norm and cross the line. It would be a shame if the existence of this global era made the younger generation have no moral values ​​in themselves. The writing method in this article is the literature method by collecting various reading sources from articles and journals which are then analyzed and then linked to the issues discussed. Based on the results of the analysis that has been carried out, the results are then discussed in this article, namely, the first is about moral values, the second is about the phenomenon of moral decline in adolescents caused by the times and globalization, the third is the importance of instilling moral values ​​in children who are carried out through education.